Expression of p53 as a biomarker in determining response to apatinib for advanced gastric cancer - Qiu, Zhiyuan; Qin, Rong; Zhang, Ziyi; Zhang, Ting; Zhang, Zhao; Qiao, Chunyue; Xi, Yan; Tian, Guangyu; Wang, Yan (Frontiers in Oncology, 2023)
Background Apatinib has shown outstanding value in the treatment of advanced gastric cancer (AGC). However, no biomarkers are available to select AGC patients who will benefit from apatinib. The aim of the present study was to investigate the association between p53 and Ki67 expression of and the outcome in AGC patients treated with apatinib. Methods From December 2015 to December 2020, 92 AGC patients were enrolled and was retrospectively evaluated. They were given apatinib at a daily dose of 500 or 250 mg every 4 weeks to monitor clinical efficacy and adverse events (AEs). Kaplan-Meier method was used for survival analysis. Expression of p53 and Ki67 was detected by immunohistochemistry (IHC) and correlated with survival. Results Among 92 evaluable patients, the objective response rate (ORR) and disease control rate (DCR) were 17.4% and 79.3%, respectively, and none of them achieved a CR, 16 achieved a PR (17.4%) (95% CI 9.8%-26.1%). Stable disease (SD) was observed in 57.6% of patients (95% CI 49.2%-69.9%) and PD in 21.7% of patients (95% CI 13.6%-31.3%). The median progression free survival (mPFS) was 122.7 ± 8.2 days, and the median overall survival (mOS) was 203.4 ± 11.9 days. P53 expression was observed in 35 patients (38.0%) and high expression of Ki67 was detected in 34 patients (37.0%). There was a statistically significant inverse relationship between p53 and Ki67 expression (P=0.014). Moreover, p53 was significantly correlated with the OS (P=0.018), but Ki67 had no significant influence on OS. Conclusions Apatinib showed promising efficiency and was well tolerated as a second-line treatment for AGC patients. AGC patients with p53-negative were likely to benefit from apatinib treatment; however, the expression of Ki67 proteins has no significant impact on the outcome of AGC patients.